STUDI KIMIA DAN FARMAKOLOGI TANAMAN KUNYIT (Curcuma longa L) SEBAGAI TUMBUHAN OBAT SERBAGUNA - Partomuan Simanjuntak (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
Abstract Some reports indicated a great variety of pharmacological activities of kunyit, Curcuma longa L. which exhibit anti-inflamatory, anti virus, anti bacteria, antioxidant, nematocidal activities, etc. Curcuminoids are major compounds in Curcuma longa L responsible for the biological activity. This paper compiles an overview of those pharmacological activities and chemical compositions of the kunyit, Curcuma longa establishing its importance in health.Keywords: chemistry, pharmacology, Curcuma longa L, medicinal plants